ANALISIS MINAT MASYARAKAT DESA PURWOSARI KABUPATEN BUNGO MENGGUNAKAN JASA PERBANKAN SYARIAH - Sissah; Firman Syah Noor; Jumi Sari (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This research is about how the interest of the Purwosari village community in using Islamic banking in the midst of a community with a population of 6.206 souls where 85 percent are predominantly Muslim, and it is known that before further research the authors observed that the total number of transactions was 5-10 per day. So that the writer is also interested in conducting research on the interest in saving in the Purwosari village community where the majority of the people are Muslims, and the number of Bank Syarriah customers is still relatively small. Moreover, in that area there are Conventional Banks that have been established for a long time compared to Islamic Banks. The research method used is descriptive qualitative method, and the sample for this research is the entire population using purposive sampling, namely as many as 20 people. The results show that: 1) There is a lack of interest in the people of Purwosari Village, Pelepat Ilir District, in using Sharia Banking services. Because there are still many people in Purwosari Village who still make transactions at conventional banks. 2) What makes the lack of knowledge of the Purwosari village community using Islamic banking services. 3) There are several factors that influence the lack of interest of the people of Purwosari Village in using Islamic Banking services, namely internal factors, social motive factors, emotional factors, location factors, and promotion factors